Early acid/base and electrolyte changes in permanent middle cerebral artery occlusion: Aged male and female rats. Issue 1 (3rd April 2019) - Martha, Sarah R.; Collier, Lisa A.; Davis, Stephanie M.; Goodwin, Sarah J.; Powell, David; Lukins, Doug; Fraser, Justin F.; Pennypacker, Keith R.
Abstract: Background: Early changes in acid/base and electrolyte concentrations could provide insights into the development of neuropathology at the onset of stroke. We evaluated associations between acid/base and electrolyte concentrations, and outcomes in permanent middle cerebral artery occlusion (pMCAO) model. Methods: 18‐month‐old male and female Sprague‐Dawley rats underwent pMCAO. Pre‐, post‐ (7 min after occlusion), and at 72 hr of pMCAO venous blood samples provided pH, carbon dioxide, oxygen, glucose, hematocrit, hemoglobin, and electrolyte values of ionized calcium, potassium, and sodium. Multiple linear regression determined predictors of infarct and edema volumes from these values, Kaplan‐Meier curve analyzed morality between males and females at 72 hr, and a Cox regression model was used to determine predictors for mortality. Results: Analysis indicated significant differences in acid/base balance and electrolyte levels in aged rats not dependent on sex between the three time points in the pMCAO model. Changes in pH (from pre‐ to post and post‐ to 72 hr) and changes in sodium and ionized calcium (from post‐ to 72 hr) were predictors of infarct volume and edema volume, respectively. Cox Regression revealed there is a 3.25 times increased risk for mortality based on changes in bicarbonate (pre‐ to post‐MCAO). Conclusions: These early venous blood changes in acid/base balance and electrolytes can be used to predict stroke outcomes in our rat model of stroke. This study provides potential biomarkers to be examined in the human condition that could provide profound prognostic tools for stroke patients. Abstract : Early venous blood changes in acid/base balance and electrolytes can be used to predict stroke outcomes (infarct volume, edema volume, and mortality) in our rat model of stroke. If applied to the human condition, use of these electrolytes/blood gas changes could provide profound prognostic tools for stroke patients.